Effects of milling temperature and time on phase evolution of Ti-based alloy - Kristaly F.; Sveda M.; Sycheva A.; Miko T.; Racz A.; Karacs G.; Janovszky D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Ti50Cu25Ni20Sn5 (at.%) powder was subjected to high-energy ball milling at room temperature and -78 °C. As a function of the milling time, evaluation of phases, morphology, and the refinement of grain size were investigated by scanning electron microscopy (SEM) and X-ray diffraction analysis (XRD), differential scanning calorimetry (DSC), transmission electron microscopy (TEM), and laser-diffraction particle size analysis (PSA). The transformation of the crystalline structure into an amorphous structure and then the transformation into a nanocrystalline structure during further milling was detected. The stress-induced martensitic transformation occurred after 30 min milling time at both temperatures, the cubic Cu(Ni,Cu)Ti2 phase transformed into the orthogonal structure. The hardness value of powders after 150 min milling time increased from 506 to 780 HV0.01. The milling temperature did not significantly influence the amount of amorphous fraction (33-36 wt.%), however, the composition of amorphous content was more influenced by temperature. The interval of crystallite size was between 1.2 and 11.7 nm after 180 min of milling. The amount and the cell parameters of the Sncontaining phases were different for the two milling experiments because the diffusion coefficients of the Sn atom differed to a large extent.